VocBlast: A Preview of a Mobile Vocabulary Application to Learn Specialized Engineering Vocabulary - Zuraina, Ali; Mohd Amir Izuddin, Mohamad Ghazali; Supyan, Hussin; Ahmad Fauzi, Mohd Ayub; Hafizoah, Kassim; Nadia, Muhammad; Rosnani, Ismail; Siti Norzaimalina, Abd Majid (2015)
There is a growing body of literature that recognizes the integration of mobile devices in language learning. Mobile devices is of interest in language learning is because of its portability and efficiency. VocBlast, a newly-developed engineering vocabulary mobile application (app), is developed to assist engineering students at tertiary level to improve their mastery of English language. The objective of the paper is to review the concept and content of the app. VocBlast consisted of 10 different vocabulary games that are designed to accommodate the language learning experience of the engineering students. As for the content of the app, the vocabulary is derived from engineering textbooks. Although VocBlast is still in the progress of development, it can be stated that the app may facilitate learners to enrich their specialized vocabulary. As a new alternative for learners to diversify their vocabulary learning experience, VocBlast allows the learner to not only learn specialized vocabulary but also its definition and application. Thus, this will enrich their specialized vocabulary knowledge and at the same time, provide the learner an opportunity to learn in an interactive and fun environment.